Writing information transfers for out-of-hours palliative care: a controlled trial among GPs - Bart Schweitzer; Nettie Blankenstein; Willemjan Slort; Dirk L. Knol; Luc Deliens; Henriette Van Der Horst (Taylor & Francis Group, 2016)
Objective: The aim was to evaluate the effect of the implementation of an information handover form regarding patients receiving palliative care. Outcome was the information available for the out-of-hours GP co-operative. Design: We conducted a controlled trial. Setting: All GPs in Amsterdam, The Netherlands. Intervention: The experimental group (N = 240) received an information handover form and an invitation for a one-hour training, the control group (N =  186) did not receive a handover form or training. We studied contacts with the GP co-operative concerning patients in palliative care for the presence and quality of information transferred by the patient's own GP. Main outcome measures: Proportion of contacts in which information was available and proportion of adequate information transfer. Results. Overall information was transferred by the GPs in 179 of the 772 first palliative contacts (23.2%). The number of contacts in the experimental group in which information was available increased significantly after intervention from 21% to 30%, compared to a decrease from 23% to 19% in the control group. The training had no additional effect. The content of the transferred information was adequate in 61.5%. There was no significant difference in the quality of the content between the groups. Conclusion: The introduction of a handover form resulted in a moderate increase of information transfers to the GP co-operative. However, the total percentage of contacts in which this information was present remained rather low. GP co-operatives should develop additional policies to improve information transfer. Key Points  The out-of-hours period is potentially problematic for the delivery of optimal palliative care, often due to inadequate information transfer.  Introduction of a handover form resulted in a moderate increase of transferred information.  The percentage of palliative contacts remained low in cases where information was available.  Adequate information was transferred in more than half of the cases.